Students’ Perspective on Using Technology to Improve Translation Quality in Translation Classes - Maulud, Ismail; Mahmud, Fitriningsih Pratiwi; Talaohu, Ahmad Rifani (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2025)
Translation plays a vital role in bridging languages and cultures, and the rapid development of translation technologies has created new opportunities and challenges in translator education. This study aimed to explore students’ perspectives on how the use of technology improves their translation quality in university-level translation classes, with a focus on accuracy, fluency, and efficiency, while also examining the barriers students face. A qualitative research design was employed with purposive sampling of 46 students from two translation classes in the English Department of Universitas Khairun. Data were collected through participatory observation, semi-structured interviews, and student translation outputs, and analyzed thematically. Findings reveal that based on students’ experiences, technology enhances translation accuracy, fluency, and efficiency, although barriers such as inadequate training and over-reliance persist. The study recommends comprehensive technological integration into the curriculum, supported by appropriate pedagogical strategies. In conclusion, the research underscores that effective and reflective use of technology can transform translation education by cultivating digitally competent, autonomous, and critically engaged translators ready for the professional field.